Das interseções temporais em Outrora Agora, de Augusto Abelaira - Correia, Alessandro Barbosa (2008)
This work tries to analyze the factor time in the composition of the Formerly Now novel, of Augusto Abelaira. Initially, it tries to arrive to a conception of time in the speech, observing its ideological configuration when of the interferences present-past-future and, whenever possible, discussing concepts to this thematic one related, such as: fiction goal graphic historic, history goal and memory. The time of the novel doesn't differ a lot of the real time lived by the contemporary Portuguese society, still marked by the history of an overpowering dictatorship, thirsty of new senses, new directions for the present and the future. In a second moment, the dissertation is devoted to observe the time in the surface of the word-perfect structure, being taken into account the conditioning of this configured time and refigurative in the art of counting. Specifically, the analysis relapses on the narrative focus guided by the temporary slope, that, in some way, it guides the narrator's behavior in its tense point of view and in constant movement, besides explaining the multiple narrative voices that emanate of the romance.